Multifaceted Roles of Chemokine C-X-C Motif Ligand 7 in Inflammatory Diseases and Cancer - Wu, Qianmiao; Tu, Huaijun; Li, Jian (Frontiers in Pharmacology, 2022)
Over recent years, C-X-C motif ligand 7 (CXCL7) has received widespread attention as a chemokine involved in inflammatory responses. Abnormal production of the chemokine CXCL7 has been identified in different inflammatory diseases; nevertheless, the exact role of CXCL7 in the pathogenesis of inflammatory diseases is not fully understood. Persistent infection or chronic inflammation can induce tumorigenesis and progression. Previous studies have shown that the pro-inflammatory chemokine CXCL7 is also expressed by malignant tumor cells and that binding of CXCL7 to its cognate receptors C-X-C chemokine receptor 1 (CXCR1) and C-X-C chemokine receptor 2 (CXCR2) can influence tumor biological behavior (proliferation, invasion, metastasis, and tumor angiogenesis) in an autocrine and paracrine manner. CXCL7 and its receptor CXCR1/CXCR2, which are aberrantly expressed in tumors, may represent new targets for clinical tumor immunotherapy.